Elaboración de un manual de Gestión Integral de Desechos Sólidos en el Campus Salache de la Universidad Técnica de Cotopaxi, Provincia de Cotopaxi, periodo 2017- 2018 - Quishpe Ortiz, Yajaira Karina (2018)
The present research project was based on the characterization of solid waste and environmental impact assessment for the development of an Integral Management Manual of solid waste at Salache campus of the Technical University of Cotopaxi. The study was carried out on Agricultural Sciences and Natural Resources Faculty with 2190 sitizens formed by administrators, teachers, students and staff operating. The characterization of the generated solid waste was held for two weeks; weighing executed with manual scales, where it determined the total solid waste collected 1196,89kg which means that an average of 128,54 kg/day, equivalent to 0,13 Ton/day generated. With the data obtained from the assessment and characterization was designed the Integral Management Manual of Solid Waste; containing five guidelines (environmental policy, planning, implementation and operation, checking and revision of the document) set out in the International Standard (ISO) 14001:2004; this also provided the regulations environmental force of the Ecuador applicable to the adequate management of solid waste (Constitution of the Republic of Ecuador, Environmental Organic Code (COA), Agreement Ministerial 061 Reform to Book VI of the Unified Text of Secondary Legislation of the Environment Ministry, Book VI, Annex VI); for future deployment at study area.